Introductory quantum mechanics - Liboff, Richard L., 1931-2014 (Addison-Wesley, 2003)
Elementary principles and applications to problems in one dimension -- Review of concepts of classical mechanics -- Historical review: experiments and theories -- The postulates of quantum mechanics. Operators, eigenfunctions, and eigenvalues -- Preparatory concepts. Function spaces and hermitian operators -- Superposition and compatible observables -- Time development, conservation theorems, andparity -- Additional one-dimensional problems. Bound and unbound states -- Finite potential well, periodic lattice, and some simple problems with two degrees of freedom -- Further development of the theory and applications to problems in three dimensions -- Angular momentum -- Problems in three dimensions -- Elements of matrix mechanics. Spin waverfunctions. Application to atomic, molecular, solid-state, and nuclear physics. Elements of quantum statistcs -- Perturbation theory -- Scattering in three dimensions -- Relativistic quantum mechanics -- Quantum computing.